Transcriptomic analysis reveals differential gene expression in response to aluminium in common bean (Phaseolus vulgaris) genotypes - Eticha, D; Zahn, M; Bremer, M; Yang, Z; Rangel Becerra, Andrés Felipe; Rao, Idupulapati M.; Horst, Walter J. (Oxford University Press, 2010)
Background and Aims: Aluminium (Al) resistance in common bean is known to be due to exudation of citrate from the root after a lag phase, indicating the induction of gene transcription and protein synthesis. The aims of this study were to identify Al-induced differentially expressed genes and to analyse the expression of candidate genes conferring Al resistance in bean.